2014
DOI: 10.3389/fimmu.2014.00129
|View full text |Cite
|
Sign up to set email alerts
|

Splenic B-1a Cells Expressing CD138 Spontaneously Secrete Large Amounts of Immunoglobulin in Naïve Mice

Abstract: B-1a cells constitutively secrete natural antibody that provides immediate protection against microbial pathogens and functions homeostatically to speed removal of apoptotic cell debris. Although B-1a cells are especially prominent in the peritoneal and pleural cavities, some B-1a cells reside in the spleen. A small subset of splenic B-1a cells in naïve, unimmunized mice express CD138, a recognized plasma cell antigen, whereas the bulk of splenic B-1a cells are CD138 negative. Splenic B-1a cells in toto have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 38 publications
(48 reference statements)
4
32
0
Order By: Relevance
“…Splenic CD138 + B1a cells have been identified as natural IgM-producing cells (39) and can differentiate into IgG-producing B1a cells (44). Thus, we examined whether class-switched or IgG-secreting splenic B1a cells are increased in aged Blk+/− and Blk−/− mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Splenic CD138 + B1a cells have been identified as natural IgM-producing cells (39) and can differentiate into IgG-producing B1a cells (44). Thus, we examined whether class-switched or IgG-secreting splenic B1a cells are increased in aged Blk+/− and Blk−/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…Given that class switch recombination (CSR) is applied to BCR class switching in B1 cells, IgM lo/− gated cells therefore contain class-switched cells. We modified the staining and gating strategy from Rothstein’s and Herzenberg’s groups (39, 44) and characterized splenic IgM hi CD138 + B1a cells as IgM hi IgD int/lo B220 int/hi CD5 int CD43 + CD138 + , while splenic IgM lo/− CD138 + B1a cells were characterized as IgM lo/− IgD int/lo B220 int/hi CD5 int CD43 + CD138 + (Figure 3A). Splenic IgM lo/− CD138 + B1a cells from aged Blk−/− mice, but to a lesser extent from Blk+/− mice, had significant increase of IgM lo/− CD138 + B1a cells compared to Blk+/+ mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B1 B cells can be further subdivided into B1a (CD5 ϩ ) and B1b (CD5 Ϫ ) (21). Although still debatable, it has been demonstrated that B1a cells outside of the peritoneal cavity produce the majority of the natural IgM in naïve mice independent of T cells (18,22,23), whereas B1b cells are responsible for T-independent IgM memory response (24) but are not a major source of natural IgM. How these natural IgM-producing B1a cells are regulated are also poorly understood despite the findings that antigen specificity and B cell receptor (BCR) signaling strength are critical factors in B1a cell development because deletion of BCR co-stimulatory molecules such as CD19 results in a massive reduction of B1a numbers, whereas deletion of negative regulators of BCR signaling such as Siglec-G leads to a vast increase in B1a cell population (25,26).…”
mentioning
confidence: 99%
“…In the spleens of naïve mice, Dr. Holodick and collaborators assess the origin and function of the small CD138+ B1a cell population. They show that this population is likely responsible for a substantial portion of natural IgM that differs from IgM produced by other B1a cell subsets, underlying the heterogeneity of IgM-secreting cells within B1a cells (3). Dr. Cunningham and collaborators review current knowledge on B1b cells in humans and mice, and discuss how B1 and B2 cells might interplay during the antibody response to proteins like porins from pathogenic microbes, which induce both classical T-dependent and T-independent response (4).…”
mentioning
confidence: 99%